Cos(6x)+cos(4x)=o

Simple and best practice solution for Cos(6x)+cos(4x)=o equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Cos(6x)+cos(4x)=o equation:


Simplifying
Cos(6x) + cos(4x) = o

Remove parenthesis around (6x)
osC * 6x + cos(4x) = o

Reorder the terms for easier multiplication:
6osC * x + cos(4x) = o

Multiply osC * x
6osxC + cos(4x) = o

Remove parenthesis around (4x)
6osxC + cos * 4x = o

Reorder the terms for easier multiplication:
6osxC + 4cos * x = o

Multiply cos * x
6osxC + 4cosx = o

Reorder the terms:
4cosx + 6osxC = o

Solving
4cosx + 6osxC = o

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6osxC' to each side of the equation.
4cosx + 6osxC + -6osxC = o + -6osxC

Combine like terms: 6osxC + -6osxC = 0
4cosx + 0 = o + -6osxC
4cosx = o + -6osxC

Divide each side by '4osx'.
c = 0.25s-1x-1 + -1.5C

Simplifying
c = 0.25s-1x-1 + -1.5C

Reorder the terms:
c = -1.5C + 0.25s-1x-1

See similar equations:

| (1-3x)=0 | | 2x+5x=10x+60 | | 2A+10X^4C=0 | | 12x-3y-2(4x+y)= | | 2x-20=80 | | 7x+8y+3(2x+4y)= | | 5a+7a-6b-3a= | | 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q | | 5x+12y=8400 | | 27=9s | | 10x-5=8x+15 | | (2x-3)/(5-3x)0 | | =(x+y-1)+(x+y+1)-(x+y-z) | | 4b-9b= | | 3x-20=x+8 | | 9+35r+25r=35r+34r | | x=3x^2+2x+6 | | F+2f+4f= | | x^2+y^2-10x+9y+1=0 |

Equations solver categories